The Influence of Financial Literacy, Lifestyle, and Perceptions About Sharia Banking on Students' Decisions to Use Mobile Banking Bank Sharia Indonesia - Fahmi, Hafiz Aulia; Noval, Muhammad; Widyantara, Fahreza; Mahfuzah, Annisa (Universitas Ciputra Surabaya, 2024)
This research is motivated by the influence of financial literacy, lifestyle, and perception on students' decisions to use Islamic bank mobile banking, lack of financial literacy in Islamic financial institutions where many students still do not use mobile banking by lifestyle needs. The purpose of the study is to determine the influence of financial literacy, lifestyle, and perception of Islamic banking on students' decisions to use mobile banking. This type of research is field research with a quantitative approach in the form of correlations or relationships. The data collection of this study used a questionnaire distributed to FEBI students of the Islamic Banking Department Class of 2019-2021 with a sample of 80 respondents. The results of partial research on financial literacy, and perceptions of Islamic banking have a significant positive influence. The lifestyle partially does not have a significant influence. The results of the study simultaneously financial literacy, lifestyle, and perceptions of Islamic banking have a significant influence on students' decisions to use Bank Syariah Indonesia mobile banking.